Graft Selection in Anterior Cruciate Ligament Reconstruction: A Comprehensive Review of Current Trends - Marko Ostojic; Pier Francesco Indelli; Bruno Lovrekovic; Jerome Volcarenghi; Doria Juric; Hassan Tarek Hakam; Mikhail Salzmann; Nikolai Ramadanov; Aleksandra Królikowska; Roland Becker; Robert Prill (Medicina, 2024)
Anterior cruciate ligament (ACL) injuries are common in sports and often require surgical intervention, e.g., ACL reconstruction (ACLR), aimed at restoring knee stability and enabling a return to pre-injury activity levels. The choice of graft is crucial, impacting biomechanical properties, clinical outcomes, and complication rates, and is especially important in revision surgeries after graft failure. Over the past 30 years, trends in graft selection have evolved towards more individualized approaches, considering factors such as patient activity level, prior injuries, and tissue availability. In Europe, autografts like hamstring tendon (HT), bone-patellar tendon-bone (BTB), and quadriceps tendon (QT) are preferred, with the increasing use of QT grafts. This review synthesizes the current literature on graft selection and its influence on ACLR outcomes.